HLA-G1+ Expression in GGTA1KO Pigs Suppresses Human and Monkey Anti-Pig T, B and NK Cell Responses - Rao, Joseph Sushil; Hosny, Nora; Kumbha, Ramesh; Naqvi, Raza Ali; Singh, Amar; Swanson, Zachary; Levy, Heather; Matson, Anders W.; Steinhoff, Magie; Forneris, Nicole; Walters, Eric; Hering, Bernhard J.; et al. (Frontiers in Immunology, 2021)
The human leukocyte antigen G1 (HLA-G1), a non-classical class I major histocompatibility complex (MHC-I) protein, is a potent immunomodulatory molecule at the maternal/fetal interface and other environments to regulate the cellular immune response. We created GGTA1-/HLAG1+ pigs to explore their use as organ and cell donors that may extend xenograft survival and function in both preclinical nonhuman primate (NHP) models and future clinical trials. In the present study, HLA-G1 was expressed from the porcine ROSA26 locus by homology directed repair (HDR) mediated knock-in (KI) with simultaneous deletion of α-1-3-galactotransferase gene (GGTA1; GTKO) using the clustered regularly interspersed palindromic repeats (CRISPR)/CRISPR associated protein 9 (Cas9) (CRISPR/Cas9) gene-editing system. GTKO/HLAG1+ pigs showing immune inhibitory functions were generated through somatic cell nuclear transfer (SCNT). The presence of HLA-G1 at the ROSA26 locus and the deletion of GGTA1 were confirmed by next generation sequencing (NGS) and Sanger’s sequencing. Fibroblasts from piglets, biopsies from transplantable organs, and islets were positive for HLA-G1 expression by confocal microscopy, flow cytometry, or q-PCR. The expression of cell surface HLA-G1 molecule associated with endogenous beta-2-microglobulin (beta-2m) was confirmed by staining genetically engineered cells with fluorescent labeled recombinant ILT2 protein. Fibroblasts obtained from GTKO/HLAG1+ pigs were shown to modulate the immune response by lowering IFN-γ production by T cells and proliferation of CD4+ and CD8+ T cells, B cells and natural killer (NK) cells, as well as by augmenting phosphorylation of Src homology region 2 domain-containing phosphatase-2 (SHP-2), which plays a central role in immune suppression. Islets isolated from GTKO/HLA-G1+ genetically engineered pigs and transplanted into streptozotocin-diabetic nude mice restored normoglycemia, suggesting that the expression of HLA-G1 did not interfere with their ability to reverse diabetes. The findings presented here suggest that the HLA-G1+ transgene can be stably expressed from the ROSA26 locus of non-fetal maternal tissue at the cell surface. By providing an immunomodulatory signal, expression of HLA-G1+ may extend survival of porcine pancreatic islet and organ xenografts.